Evaluation of sesame genotypes for field resistance against Antigastra catalaunalis, Macrophomina phaseolina and Phyllody: Field Resistance in Sesame against Diseases - Pandey, Shalini; Neelam Geat; Rekha Kumawat; M.M. Sundria; Sitaram Kumhar (Annals of Arid Zone, 2023)
One hundred three genotypes of sesame (Sesamum indicum L.) representing varied geographic and genetic diversity were tested against major insect pests and diseases. None of the evaluated genotypes were found to be free from infestation by leaf webber and capsule borer, (Antigastra catalaunalis). The average plant, flower and capsule damage varied from zero to 50%, 6.85% to 57.14% and 4.23% to 88.89%, respectively. Three genotypes viz., S-0292, IC-131943 and S-0301 were found moderately resistant to A. catalaunalis at all the three stages (vegetative, flower and capsule stages). Among the 103 genotypes evaluated for Macrophomina stem & root rot and phyllody disease, 11 genotypes namely S-0644, KMR-53, IS-1672, NIC-16256, IS-245, TC-30, IC-131943, EC-334974, NIC-7935, GRT-8245, and NIC-8439-B showed excellent performance with less disease incidence.